Answer:
C: tan 60 = √3
Step-by-step explanation:
Let the adjacent part of the triangle be x and let the opposite side be y.
Thus, from trigonometric ratios;
x/10 = cos 60
We are given cos 60 = ½
Thus;
x/10 = ½
x = ½ × 10
x = 5
Similarly;
y/10 = sin 60
Now,from trigonometric relationship we know that; sin 60 = cos 30. Thus;
y/10 = cos 30
We are given cos 30 = (√3)/2
Thus;
y/10 = (√3)/2
y = 10 × (√3)/2
y = 5√3
Since it is a right angle triangle with one angle being 60°, it means the other one is 30° since sum of angles in a triangle is 180°.
Thus;
5/(5√3) = tan 30°
1/√3 = tan 30
Similarly;
5/10 = sin 60°
sin 60° = ½
Also;
tan 60 = (5√3)/5
tan 60 = √3
Also;
sin 30 = 5/10
sin 30 = ½
Looking at the options, the only correct one is Option C
Answer: The annual interest rate is 1.06%
Step-by-step explanation: This is a simple interest computation.
The formular for a simple interest is given as;
I = (P ×R × T)/100
Where I represents the interest paid,
P represents Principal borrowed at the beginning
R represents the rate at which the interest is calculated
T represents the Time measured in number of years
If the interest is calculated as I = (P×R×T)/100, we should first of all make R the subject of the formular;
Multiply both sides by 100
100I = P×R×T
Divide both sides of the equation by P and T
(100I)/(P × T) = R
Now we can insert the values into the rearranged formular
(100 × 143)/(4500 × 3) = R
14,300/13,500 = R
143/135 = R
1.0592592593 = R
Therefore, R which is the rate of interest equals approximately 1.06%
Answer with Step-by-step explanation:
Let the ones digit of the number be y
and tens digit of the number be x.
The tens digit is two less than the units digit.
i.e. x=y-2
The value of the number exceeds twice the sum of its digits by 19.
i.e. 10x+y=2(x+y)+19
10(y-2)+y=2(y-2+y)+19
10y-20+y=2(2y-2)+19
11y-20=4y-4+19
11y-4y=20-4+19
7y=35
dividing both sides by 7, we get
y=5
Putting value of y in x=y-2, we get
x=3
10x+y=10×3+5
=35
Hence, the two digit number is:
35
Solve the differential equations.
dy = 4 − x
/
dx
We have dy/dx = (4-x) dx which is a first order linear ODE
dy = (4-x) dx. Now integrating both sides we get:
y = 4x - 1/2 x^2 + C
which is the answer. Note we only wrote +c once since we can combine arbitrary constants under addition and subtraction with each other.